2014
DOI: 10.1179/1743132814y.0000000458
|View full text |Cite
|
Sign up to set email alerts
|

Academic self-concept in children with epilepsy and its relation to their quality of life

Abstract: The presented results suggest that considerable attention should be paid to the role of academic self-concept in education of children with epilepsy and to the factors influencing this self-concept in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Children who achieved very good results in their ability to fulfil societal norms but their academic self-concept was very low have been reported [20] . Our recent paper shows that the academic self-concept of CWE is on average significantly lower than in their peers without seizures and is closely related to their quality of life [10] . Complex analysis shows that lower self-concept of CWE is due to high fraction of CWE having LD and/or intellectual disability.…”
Section: A C a D E M I C A C H I E V E M E N T A N D Academic Self-comentioning
confidence: 88%
See 1 more Smart Citation
“…Children who achieved very good results in their ability to fulfil societal norms but their academic self-concept was very low have been reported [20] . Our recent paper shows that the academic self-concept of CWE is on average significantly lower than in their peers without seizures and is closely related to their quality of life [10] . Complex analysis shows that lower self-concept of CWE is due to high fraction of CWE having LD and/or intellectual disability.…”
Section: A C a D E M I C A C H I E V E M E N T A N D Academic Self-comentioning
confidence: 88%
“…Bozkala et al then reported that an educational program focused on high-school students in Turkey was associated with significant increase in knowledge of epilepsy and more positive attitudes towards people with epilepsy [35] . Our recent study shows that teachers of CWE may have serious problems to assess correctly their abilities [10] . Certain antiepileptic drugs may have adverse side effects, such as decreasing the ability of the affected children to concentrate [11] .…”
Section: Role Played By Classmates and Parents Of Children With Epilepsymentioning
confidence: 98%
“…We obtained consent from parents of all children included in the study. The procedure has previously been described in more detail in our previous paper (Brabcová et al, 2015).…”
Section: Procedures and Participantsmentioning
confidence: 99%
“…Following up on our recent paper (Brabcová , Kršek, Kohout, Jošt, & Zá rubová , 2015), the main aims of the current study were (1) to determine effects of various factors on academic self-concept in children with epilepsy, (2) having identified LD as the most significant factor in our analysis, to compare academic self-concept in children with epilepsy combined with a learning disability (hereafter denoted CWE + LD) and children with epilepsy but without a learning disability (hereafter denoted CWE À LD), and (3) to analyze possible correlations between academic self-concept and quality of life in both groups of CWE.…”
mentioning
confidence: 98%
“…Enhancing the academic self-concept of students with special educational needs is very crucial because it is associated with their quality of life. [ 1 ] Academic self-concept is a domain of the composite construct of self-concept, and it refers to a student's perceived ability to succeed in a specific academic domain (e.g., physical education). It is shaped by academically oriented interactions with fellow students, teachers, and parents.…”
Section: Introductionmentioning
confidence: 99%